Kedudukan Mahkamah Syariah Aceh untuk Menggantikan Peran Peradilan Agama dalam menjalankan Kekuasaan Kehakiman - Muhammad Rayhan Putera; M. Junaidi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The Aceh Sharia Court is a special judicial institution formed based on the specifics of Aceh as regulated in the Aceh Government Law. The existence of the Aceh Sharia Court has juridical consequences for the exercise of judicial power which was previously exercised by the Religious Courts. This research aims to analyze the position of the Aceh Sharia Court in the national justice system and examine its power in replacing the authority of the Religious Courts in handling cases related to Islamic law. The research method used is normative legal research. The research results show that the Aceh Sharia Court has an equal position to the Religious Court in the judicial power structure, but has broader authority because it covers Islamic civil cases, sharia criminal (jinayat), and sharia procedural law. This transfer of authority does not eliminate the existence of the Religious Courts nationally, but creates a special justice system that only applies in the Aceh region. The position of the Aceh Sharia Court strengthens the implementation of Islamic law within the framework of the Unitary State of the Republic of Indonesia and remains under the guidance of the Supreme Court.